Ludovico Agostini's 'Imaginary Republic' Utopia in the Italian Renaissance - Donato, Antonio (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
This book offers the first English translation and comprehensive analysis (inclusive of introductory study and endnotes to the translation) of the longest and most complex Italian Renaissance utopia, Ludovico Agostini's Imaginary Republic. It not only reveals the significance of a text that has been mostly forgotten; it also shows how an investigation of Imaginary Republic uncovers neglected and surprising facets of Renaissance utopianism. The current scholarly image of Renaissance utopianism is based, predominantly, on English texts. Other European utopian traditions are considered only tangentially and do not substantially inform the overall picture of the nature of Renaissance utopias. This book's study of Imaginary Republic, within the context of Italian sixteenth- and seventeenth-century utopias, contributes to filling this gap in the critical literature by expanding the current understanding of Renaissance utopianism. Antonio Donato is Associate Professor of Medieval and Renaissance Philosophy at Queens College, City University of New York, USA. He is the author of Boethius' Consolation of Philosophy as a Product of Late Antiquity (2013), Italian Renaissance Utopias: Doni, Patrizi, and Zuccolo (Palgrave, 2019), and Boezio. Un pensatore tardoantico e il suo mondo (2021).
CHAPTER I: Introduction -- PART I: Ludovico Agostini's Imaginary Republic and Italian Renaissance Utopianism -- CHAPTER II: Searching for Italian Renaissance Utopias.-CHAPTER III: Ludovico Agostini and his Time -- CHAPTER IV: The Imaginary Republic and Agostini's Utopianism.-PART II: Ludovico Agostini's Imaginary Republic: Translation and Endnotes -- CHAPTER V: The Origin of Laws and Utopia.-CHAPTER VI: The Cardinal Virtues -- CHAPTER VII: The Imaginary Society I: The Health System -- CHAPTER VIII: The Imaginary Society II: The Political System and the Military Organisation.-CHAPTER IX: The Ideal City III" with "The Imaginary Society III: The Economic System.
Keywords: Europe -- History; Civilization -- History; Intellectual life -- History; Philosophy, Renaissance; European History; Cultural History; Intellectual History; Renaissance Philosophy